URBAN SUSTAINABILITY: TOWARDS UNDERSTANDING THE STATUS OF ZARIA URBAN AREA-NIGERIA - Murtala, Muhammad Tukur; Uthman, Muhammad; Muktar, Ahmad (FUDMA JOURNAL OF SCIENCES, 2023)
Globally, the sustainability of the urban areas has become an issue with alarming concern. However, the status of most cities in the world remain unknown, with more effort geared toward the cities of the advanced countries, so as to create sustainability rankings. Conversely, the chaos and lack of uniformity in sustainability assessment tool has also contributed to the knowledge gap. In this study, the urban sustainability of Zaria urban area was assessed, focusing on the social dimension of sustainability, due to data availability. Data available within 2018 was used for the assessment using the theme-based indicator assessment framework. Results from the study showed that out of the 14 indicators assessed, only 3 indicators can be said to have a relatively good status, for this reason the sustainability of the urban area was low, resulting to the challenges of unsustainability in the urban area.
Keywords: Urban sustainability; theme-based indicator framework; Zaria urban area